A Financial Distress Prediciton on Property, Construction, and Real Estate Companies Listed in BEI - Alberto Orson Ongkowidjojo; Anastasia Njo; Januar Budiman (Program Studi Magister Teknik Sipil - Petra Christian University, 2020)
The slowing of economic growth in Indonesia could cause financial distress for companies in property, construction and real estate sectors as these companies has enormous amount of GDP contributions in Indonesia. These difficulties are related to companies being able to accomplish all its responsibilities in short nor long terms. In assessing financial status of a company, discriminant analysis could be of use to see financial ratio such as liquidity ratio, profitability, activity and solvability. This research consists of comparative and sample pulling technique towards 81 population in multiple sectors such as property, construction and real estate. Data collection method by documentation. Discriminant analysis results depicts that liquidity ratio(CA/CL), profitability (EBIT/TA and NI/SALES), activity (SALES/TA), and solvability (BV/TL and TL/EQUITY) could be used to distinguish which company are experiencing financial distress and which are not.